Biophysical characterization of folded state type II luciferase‐like monooxygenase - Adinda Fitri Salsabila; Abidah Tauchid; Muhammad Saifur Rohman; Donny Widianto; Sebastian Margino (Universitas Gadjah Mada, 2023)
We noticed that the Priestia megaterium genome contains five Luciferase‐like monooxygenase (LLM) encoding genes, however, their functions are unknown. The objective of this work was to characterize the biophysical properties of the recombinant LLM2 from Priestia megaterium PSA10 through in vitro and in silico approaches. We successfully cloned into the pET vector system and expressed the recombinant LLM2 in Escherichia coli BL21(DE3). The recombinant LLM2 was overproduced and purified in the form of an inclusion body with a molecular weight of ±39.5 kDa when it was analyzed in 15% SDS‐PAGE. The inclusion body of recombinant LLM2 was then refolded and characterized for its biophysical properties by measuring the UV spectrum of 200 to 250 nm wavelength and determining the change of enthalpy (ΔH) and entropy (ΔS) at the melting temperature. The refolded recombinant LLM2 exhibited a strong spectrum at 205 nm, while the unfolded recombinant LLM2 did not. The Tm, ΔHTm, and ΔSTm values of the refolded recombinant LLM2 were determined to be 318.31±4.4 K, 11.76±1.3 kJ.mol‐1, and (3.74±0.48)x10‐2 kJ.mol‐1.K‐1, respectively. The predicted 3D structure of LLM2 showed that the protein contains the TIM‐barrel, resembling the common global fold of bacterial luciferases. Determination of the cofactor preference suggested that the LLM2 preferred FAD for its cofactor.